Just in time for Christmas - Brown, Carolyn, 1948- (Sourcebooks Casablanca, 2022)
Footloose Liz Hanson has finally come home to Ringgold, Texas with a hankering to settle down. All she wants for Christmas is a house of her own-and the man of her dreams. The house was easy. Now she's got her sights set on her extremely attractive neighbor Raylen O'Donnell, her teen crush all grown up, to make her Christmas dreams come true.